Valsalva sine rupture: A case report - Paredes-Muñoz, Martín Abel (2020)
Valsalva sinus aneurysm in an infrequent entity, the incidence is 0.09 to 0.15%, most of the patients are asymptomatic while the aneurysm is intact. A rapidly progressive heart failure follows the perforation of it. We report here the case of a 27-year-old male patient presenting with a rupture Valsalva sinus aneurysm and performed a literature review.